Effect of Free Radical-Mediated Conjugation with Rosmarinic Acid on Allergenicity and Functional Properties of Egg White Protein - LIU Ying, CHEN Shiyun, GUO Xiao, HAO Yacheng, FANG Min, LIU Xin, GONG Zhiyong, YANG Qing (Shipin Kexue)
In this study, egg white protein (EWP) was covalently coupled with rosmarinic acid (RA) by a free radical method, and the coupling effect was verified by sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE) and RA binding equivalent. Fourier transform infrared spectroscopy (FTIR), circular dichroism (CD) spectroscopy, fluorescence and ultraviolet absorption spectroscopy were used to analyze the structural changes. The antioxidant capacity, antigenicity, and functional properties of EWP-RA complexes were evaluated through 1,1-diphenyl-2-picrylhydrazyl (DPPH) radical, 2,2’-azino-bis(3-ethylbenzothiazoline-6-sulfonic acid) (ABTS) radical cation scavenging assays, enzyme-linked immunosorbent assay (ELISA), and emulsification performance measurements. The results indicated that EWP-RA complexes underwent significant structural changes compared with EWP, resulting in altered antioxidant capacity and emulsifying ability. The EWP-0.2% RA complex scavenged 58.59% of DPPH radical and 72.08% of ABTS radical cation. The binding affinity of EWP to immunoglobulin (Ig) G and IgE antibodies in egg allergic patients was significantly reduced after conjugation with RA, indicating a decreased potential for antigen binding. The emulsifying activity index and emulsion stability index of the EWP-0.2% RA complex were 1.21 m2/g and 64.20 min, respectively. RA modification effectively enhanced the emulsifying capacity and emulsion stability of EWP. This study provides a theoretical basis for the covalent modification of EWP with polyphenols using the free radical method.